2015
DOI: 10.1186/s12889-015-1361-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of tobacco smoking among rural-to-urban migrant workers: a cross-sectional survey in Shanghai

Abstract: BackgroundAlthough there are several studies to investigate the smoking behaviors among rural-to-urban Chinese migrants, no study has focused individually on this population in Shanghai. This study was performed to estimate the prevalence and identify the determinants of tobacco smoking among rural-to-urban migrants in Shanghai.MethodsIn this cross-sectional study, multi-stage quota sampling was used to select 5,856 rural-to-urban migrants aged 18 years or older from seven districts in Shanghai between July an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 23 publications
7
40
1
4
Order By: Relevance
“…Multivariate analysis revealed smoking in female migrants to be significantly associated with working at construction (OR 8.08), hotels/restaurants (OR 5.06), and the entertainment sector (OR 6.79). The male migrants working at construction (OR 1.30), entertainment sector (OR 1.86), being divorced (OR 2.20), with duration of migration of four or more than four years (OR 1.42), and number of migratory cities of three or more than three (OR 1.42) showed an excess smoking prevalence [70].…”
Section: Alcohol and Nicotine Abusementioning
confidence: 99%
“…Multivariate analysis revealed smoking in female migrants to be significantly associated with working at construction (OR 8.08), hotels/restaurants (OR 5.06), and the entertainment sector (OR 6.79). The male migrants working at construction (OR 1.30), entertainment sector (OR 1.86), being divorced (OR 2.20), with duration of migration of four or more than four years (OR 1.42), and number of migratory cities of three or more than three (OR 1.42) showed an excess smoking prevalence [70].…”
Section: Alcohol and Nicotine Abusementioning
confidence: 99%
“…In this respect, our work provides a useful empirical input to a current policy issue. Researchers who study public health in China have expressed concern that rural to urban migration in that country is fueling a national smoking epidemic (Yang, Wu, Rockett, Abdullah, Beard, and Ye (), Liu et al (), Ji, Liu, Zhao, Jiang, Zeng, and Chang ()), a fact also acknowledged in a recent report by the World Health Organization (World Health Organization ()). Evidence that rural‐urban migrants suffer poorer health than their rural counterparts has also surfaced in India (Reddy, Shah, Varghese, and Ramadoss ()) and Indonesia (Lu ()).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the smoking rate among migrant workers was 32.5% (55.3% for male and 1.9% for female) [7], higher than that of the general population [2]. Many socioeconomic factors such as poor education [6], work pressure [8], as well as migration-related features [8,9] such as the numbers of migratory cities and the duration of stay, contributed to the high smoking prevalence.…”
Section: Introductionmentioning
confidence: 99%